A rare case of thyroid storm following caesarean section - Singh, Sanjay; Biswas, Manash; Jose, Tony; Dey, Madhusudan; Saraswat, Monica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Thyroid storm in pregnancy is a rare life threatening emergency, with very high maternal and perinatal mortality and morbidity. Here we present an unusual case of a 30 year-old G2P1L1 woman, a known case of post caesarean pregnancy with hyperthyroidism who presented with severe preeclampsia and on second post op day developed thyroid storm. Early recognition and timely institution of appropriate management resulted in good outcome in this case.